Memaksimalkan Gaya Kepemimpinan dan Kepuasan Kerja untuk Menurunkan Turnover Intention Karyawan - Ratnadi, Ni Kadek Ayuning; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Employee turnover can be predicted by knowing turnover intention and factors that can suppress turnover intention. The purpose of this study was to determine the effect of leadership style on turnover intention either directly or through job satisfaction mediation. This research was conducted at the Pasar Srinadi Klungkung Cooperative for 43 employees and by using the census method, all employees were involved as respondents. The data was collected using the interview method and a questionnaire using a five-choice Likert Scale. The instrument test was carried out by testing the validity and reliability with SPSS software. The data analysis technique used is path analysis and Sobel test to test mediation which is carried out with SPSS software. The results of the study prove that leadership style and job satisfaction have a negative and significant effect on turnover intention. Leadership style has a positive and significant effect on job satisfaction. The results of the mediation test prove that job satisfaction mediates the effect of leadership style on turnover intention.